2005
DOI: 10.1111/j.1744-7410.2005.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasite‐mediated shell alterations in Recent and Holocene sub‐Antarctic bivalves: the parasite as modeler of host reaction

Abstract: Abstract. New data on shell reactions elicited by larval digeneans in bivalves from Recent sub‐Antarctic populations and late Holocene Patagonian deposits are reported. Shell alterations, which are traces of digenean trematode infections, were found affecting intertidal bivalve populations from Malvinas (Falkland) Islands, Burdwood Bank, Beagle Channel, and from Holocene deposits at Tierra del Fuego (Argentina). The bivalve species involved belonged to the families Nuculanidae, Cyamiidae, and Neoleptonidae. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 15 publications
1
30
0
5
Order By: Relevance
“…It is tempting to attribute Housean (Type 1-3) and Opitzian (Type 4) blister pearls to parasitic flatworms as they are known to cause shell concretions (mostly after death of the parasite: compare Lauckner 1983) in living bivalves, but so far no identical structures are known from extant cephalopods and the identity of these Devonian parasites remains a mystery. Other structures like igloo-shaped concretions can be formed when both the bivalve and parasite are alive (Ituarte et al 2001(Ituarte et al , 2005. The types of pearls correspond well with large groups of ammonoids suggesting a certain degree of parasite-host coevolution (De Baets et al 2011;Fig.…”
Section: Pearl Formationmentioning
confidence: 98%
See 1 more Smart Citation
“…It is tempting to attribute Housean (Type 1-3) and Opitzian (Type 4) blister pearls to parasitic flatworms as they are known to cause shell concretions (mostly after death of the parasite: compare Lauckner 1983) in living bivalves, but so far no identical structures are known from extant cephalopods and the identity of these Devonian parasites remains a mystery. Other structures like igloo-shaped concretions can be formed when both the bivalve and parasite are alive (Ituarte et al 2001(Ituarte et al , 2005. The types of pearls correspond well with large groups of ammonoids suggesting a certain degree of parasite-host coevolution (De Baets et al 2011;Fig.…”
Section: Pearl Formationmentioning
confidence: 98%
“…Nevertheless, various other parasitic organisms such as fungi, unicellular organisms, nematodes or arthropods (and their eggs) as well as various other irritants including inorganic material which get stuck between mantle and shell can induce pearl formation (Götting 1974(Götting , 1979Lauckner 1983). Nevertheless, the morphology of some parasite-induced structures in extant bivalves are believed to be very specific to parasitic flatworms such as pits in shells and igloo-shaped shell secretions or to polychaete worms such as borings and can be traced back in the fossil record (Liljedahl 1985, Ruiz andLindberg 1989;Ituarte et al 2001Ituarte et al , 2005Huntley 2007;De Baets et al 2011). Blister pearls (Fig.…”
Section: Pearl Formationmentioning
confidence: 98%
“…This is not straightforward since it has been demonstrated that the remains of soft-bodied helminths can be destroyed during the pearl formation process (Lauckner, 1983). However, other pathologies are believed to be more characteristic for particular lineages of parasitic flatworms such as Gymnophallidae including shell pits (Ruiz and Lindberg, 1989;Ruiz, 1991;Huntley, 2007;Todd and Harper, 2011, Figure 1(e); Huntley and Scarponi, 2012;Huntley et al, 2014;Huntley and Scarponi, 2015;Huntley and De Baets, 2015) and volcano-to igloo-shaped calcareous concretions (Campbell, 1985;Ituarte et al, 2001Ituarte et al, , 2005; Figure 2(aec); Huntley and De Baets, 2015). Ituarte et al (2001Ituarte et al ( , 2005) demonstrated a link between igloo-shaped concretions and gymnophallid digenean flatworms, which these authors traced back to 6400 years in the Holocene.…”
Section: Silurian Blister Pearls and Calcareous Concretions In Bivalvmentioning
confidence: 95%
“…As (blister) pearls and volcano-to igloo-shaped concretions can be induced by intermediate stages of parasitic flatworms (G€ otting, 1974, 1979Lauckner, 1983;Campbell, 1985;Ituarte et al, 2001Ituarte et al, , 2005, their first occurrence in the Silurian (K rí z, 1979;Liljedahl, 1985Liljedahl, , 1994De Baets et al, 2011) might already indicate the presence of derived parasitic flatworms in the Silurian. Pearls and blisters can, however, be caused by a variety of irritants, including other parasites, shell burrowing organisms and inorganic particles (G€ otting, 1974;Lauckner, 1983).…”
Section: Silurian Blister Pearls and Calcareous Concretions In Bivalvmentioning
confidence: 96%
See 1 more Smart Citation